Total leukocyte count-based predictor tool for calculating hematopoietic progenitor cell dose in bone-marrow harvest - Dinesh Arora (Global Journal of Transfusion Medicine, 2017)
Background: Hematopoietic progenitor cell transplantation is increasingly being used as the curative therapy in India for various clinical conditions. There are three main sources of hematopoietic progenitor cells; hematopoietic progenitor cell-apheresis (HPC-A), hematopoietic progenitor cell-bone marrow (HPC-M) and hematopoietic progenitor cell-Umbilical Cord (HPC-C). The number of CD34+ cells in HPC-C is fixed. In HPC-A, the number of CD34+ cells collected is based on the baseline peripheral blood counts and a second harvest can be easily performed. The trickiest calculation of CD34+ cells adequacy is in case of HPC-M harvest, where the end point of harvest cannot be predetermined. Aim: The aim was to study the accuracy of a total leukocyte count (TLC)-based predictor tool in predicting CD34+ dose in comparison to the actual CD34+ cell counts in the harvest. Materials and Methods: This was a prospective study to validate the tool. The data captured included patient and donor demographic data, disease condition, mobilization regimen of the donor, progenitor cell harvest data, dose collected, cryopreservation if any, progenitor cell infusion data, engraftment, and follow-up of the patient including day thirty and day hundred chimerism in a tertiary care hospital. Results: Five patients were included in the study. For each patient, the target dose and volume were collected in a single HPC-M harvest attempt, and no repeat harvests were required. The average volume of HPC-M harvest collected was 195 ml. The average CD-34+ cell dose in HPC-M harvest achieved was 4.3 × 106/kg (Range = 3.39–6.42). This was 85.7% of the targeted dose calculated on the basis of TLC-based predictor tool. Conclusion: This study reiterates the importance of a simple TLC-based predictor tool (formula) for estimation of HPC-M volume to be harvested.